PERSPECTIVES ON SUSTAINABLE PERFORMANCE START-UPS INFLUENCED BY ENTREPRENEURIAL ECOSYSTEMS AND DISRUPTIVE INNOVATION - Riyanto, Slamet (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study is to determine the factors that determine the sustainable performance of startups in terms of entrepreneurial ecosystems, the phenomenon of disruptive innovation. The research method uses the systematic literature review (SLR) method approach , where the articles reviewed are articles that have been published in reputable international journals and national journals published in 2017-2023. The results of this study indicate that the success of sustainable startup performance will be influenced by entrepreneurial ecosystems which are supported by the implementation of cultural values, human capital, robust markets, support services and local customers. The second is disruptive innovation activities. This innovation is carried out by paying attention to the conditions of new-market disruption, low-end disruption and customer disruption.